Health-Care Delay in Malignant Melanoma: Various Pathways to Diagnosis and Treatment - Senada Hajdarevic; Åsa Hörnsten; Elisabet Sundbom; Ulf Isaksson; Marcus Schmitt-Egenolf (Dermatology Research and Practice)
We aimed to describe and compare patients diagnosed with malignant melanoma (MM), depending on their initial contact with care and with regard to age, sex, and MM type and thickness, and to explore pathways and time intervals (lead times) between clinics from the initial contact to diagnosis and treatment. The sample from northern Sweden was identified via the Swedish melanoma register. Data regarding pathways in health care were retrieved from patient records. In our unselected population of 71 people diagnosed with skin melanoma of SSM and NM types, 75% of patients were primarily treated by primary health-care centres (PHCs). The time interval (delay) from primary excision until registration of the histopathological assessment in the medical records was significantly longer in PHCs than in hospital-based and dermatological clinics (Derm). Thicker tumors were more common in the PHC group. Older patients waited longer times for wide excision. Most MM are excised rapidly at PHCs, but some patients may not be diagnosed and treated in time. Delay of registration of results from histopathological assessments within PHCs seems to be an important issue for future improvement. Exploring shortcomings in MM patients’ clinical pathways is important to improve the quality of care and patient safety.